7.0k views
5 votes
What is the solution to the equation 13.7y – 10.6 = 6.2y + 19.4?  

y = 0.04

y = 0.4

y= 4

y = 40



User Dan Dye
by
6.2k points

2 Answers

0 votes

Answer:

D

Explanation:

got it right

User Nelsonvarela
by
5.0k points
2 votes

Answer:

4

Explanation:

Simplifying

13.7y + -10.6 = 6.2y + 19.4

Reorder the terms:

-10.6 + 13.7y = 6.2y + 19.4

Reorder the terms:

-10.6 + 13.7y = 19.4 + 6.2y

Solving

-10.6 + 13.7y = 19.4 + 6.2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6.2y' to each side of the equation.

-10.6 + 13.7y + -6.2y = 19.4 + 6.2y + -6.2y

Combine like terms: 13.7y + -6.2y = 7.5y

-10.6 + 7.5y = 19.4 + 6.2y + -6.2y

Combine like terms: 6.2y + -6.2y = 0.0

-10.6 + 7.5y = 19.4 + 0.0

-10.6 + 7.5y = 19.4

Add '10.6' to each side of the equation.

-10.6 + 10.6 + 7.5y = 19.4 + 10.6

Combine like terms: -10.6 + 10.6 = 0.0

0.0 + 7.5y = 19.4 + 10.6

7.5y = 19.4 + 10.6

Combine like terms: 19.4 + 10.6 = 30

7.5y = 30

Divide each side by '7.5'.

y = 4

Simplifying

y = 4

User Mlbright
by
5.3k points